Mechanisms of salinity tolerance induced by potassiumsupplementation in sugarcane varieties: morphological, physiological andnutritional responses - Silva, Antonia Almeida da (2021)
Soil salinity is one of the abiotic stresses most damaging to plant growth and development. Sugarcane (Saccharum spp.) Is a crop moderately sensitive to this abiotic stress. In order to favor their cultivation in these environments, in addition to identifying tolerant cultivars, it is important to identify mechanisms that favor the induction of tolerance in sensitive varieties. Tolerance can be induced by strengthening the nutritional status of the plant. It is known that supplementation with potassium (K+) can attenuate the negative effects of high concentration of sodium (Na+) in the soil. The entry of a greater amount of K+ under salinity conditions can maintain several of the physiological and biochemical functions attributed to it and regulate the K+ / Na+ ratio, which is considered essential for the tolerance to salt stress. Thus, the objective was to verify the supply of K+ induces tolerance to salinity, especially in sensitive sugarcane cultivars. In a first experiment, 10 varieties of Saccharum oficinarum, and the species (Saccharum spontaneum and Saccharum robustum) were used to select contrasting materials in terms of their tolerance to salinity. The plants were grown under low concentration of [Na+] (found naturally in the soil) and high [Na+] (soil enriched with 100mM NaCl). Sprout speed index, sprout percentage, plant height, stem height, number of leaves, gas exchange and biomass partition were analyzed. The results showed that the varieties presented different susceptibilities to salt stress, and that the variety SP80-3280 was the most susceptible and SP80-1816 the least susceptible, being, therefore, selected for the second study. Two varieties were grown under two [KCl] (131.4 mg/dm3; 262.8 mg/d3) and two [NaCl] (the one present in the soil 0.09 mM and 50 mM). Data were collected on plant height, stem diameter, biomass partition, photosynthesis, relative water content, leaf water potential, concentration of Ca2+, Mg2+, K+ and Na+ ions in the soil solution and in the plant, Na+/K+ ratio, histolocation of Na+ and K+ in the roots and leaves. The SP80-1816 variety achieved greater growth in treatments with greater K+ supply and was not affected by salinity. The SP80-3280 variety, on the other hand, reduced its growth under high [Na+], showing greater sensitivity to the excess of this ion, since there was a reduction in growth when subjected to salinity, regardless of the increase in K+ concentration. Therefore, considering the concentrations used, the increase in K+ in the tissues did not induce tolerance to salinity in the sensitive variety.